2012
DOI: 10.1210/jc.2011-2681
|View full text |Cite
|
Sign up to set email alerts
|

Fat Content in Liver and Skeletal Muscle Changes in a Reciprocal Manner in Patients with Acromegaly during Combination Therapy with a Somatostatin Analog and a GH Receptor Antagonist: A Randomized Clinical Trial

Abstract: Cotreatment with pegvisomant and a reduced SA dose increase IHL and decrease IMCL compared with SA monotherapy. The clinical implications remain unclear, but increased IHL may be causally linked to the transient elevations in liver enzymes observed during pegvisomant treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 40 publications
2
26
0
1
Order By: Relevance
“…A total of 20 normal-weight subjects (meanGS.E.M., BMI: 25G2) comprising ten 'young' subjects (5F/5M) with a mean (range) age of 25 (20)(21)(22)(23)(24)(25)(26)(27)(28) years and ten 'old' subjects (5F/5M) with a mean age of 65 (60-72) years participated in this study. None were smokers or receiving prescribed drugs, and none of the females received estrogen supplementation.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 20 normal-weight subjects (meanGS.E.M., BMI: 25G2) comprising ten 'young' subjects (5F/5M) with a mean (range) age of 25 (20)(21)(22)(23)(24)(25)(26)(27)(28) years and ten 'old' subjects (5F/5M) with a mean age of 65 (60-72) years participated in this study. None were smokers or receiving prescribed drugs, and none of the females received estrogen supplementation.…”
Section: Subjectsmentioning
confidence: 99%
“…MR spectroscopy was performed using a Signa Excite 1.5 tesla twin-speed scanner (GE Medical Systems) to quantify fat in muscle (IMCL) and liver (IHL) as described previously (22,23). The spectra were quantified using the LC model software package (LCModel6.2; Stephen Provencher, Oakville, ON, Canada) by means of dedicated muscle and liver spectroscopy fitting models.…”
Section: Body Composition and Physical Fitnessmentioning
confidence: 99%
“…However, untreated acromegaly is associated with raised serum TGs (64) and IR and a high visceral adiposity index (65). Perhaps unexpectedly, a single study has shown that co-treatment of acromegaly with a somatostatin analogue and the GH receptor antagonist, pegvisomant, increases intrahepatic lipid (66), but further studies are clearly warranted.…”
Section: Oestrogensmentioning
confidence: 99%
“…55 A transient increase in liver transaminases is observed in 25% of patients. 70 The mechanism is currently unknown, but a cross-sectional study recently found an association between the risk of hepatocellular injury and genetic polymorphisms associated with Gilbert's disease. 71 A more severe transaminitis (greater than three times the upper limit of normal) can be seen in 2.5% of patients and seems to be more prevalent in patients concurrently treated with somatostatin analogs.…”
Section: Pegvisomant: Metabolic and Cardiac Effectsmentioning
confidence: 99%
“…60 Cotreatment with pegvisomant and somatostatin analogs was recently shown to increase intrahepatic lipid and decrease intramyocellular lipid compared to somatostatin analog therapy alone, which may serve as a possible explanation. 70 …”
Section: Pegvisomant: Metabolic and Cardiac Effectsmentioning
confidence: 99%